2021
DOI: 10.1371/journal.pone.0252647
|View full text |Cite
|
Sign up to set email alerts
|

Co-expression analysis identifies neuro-inflammation as a driver of sensory neuron aging in Aplysia californica

Abstract: Aging of the nervous system is typified by depressed metabolism, compromised proteostasis, and increased inflammation that results in cognitive impairment. Differential expression analysis is a popular technique for exploring the molecular underpinnings of neural aging, but technical drawbacks of the methodology often obscure larger expression patterns. Co-expression analysis offers a robust alternative that allows for identification of networks of genes and their putative central regulators. In an effort to e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 320 publications
0
2
0
Order By: Relevance
“…Animal age in this study was determined by the chronological age as well as the significant decline in performance of reflex behaviors beginning at the age of 12 months ( Figure 2 ). Our laboratory demonstrated that performance in these behaviors declines in a predictable manner with age ( Kempsell and Fieber, 2014 ) and that declining performance is accompanied by a decline in excitability of PVC sensory neurons that control tail withdrawal, decreased short-term facilitation (STF) between tail sensory and motor neurons ( Kempsell and Fieber, 2015 ), decreased expression of ionotropic glutamate receptor subunits ( Greer et al, 2019 ), and other changes in gene expression that alter proteostasis and increase neuro-inflammation ( Kron et al, 2020 ; Kron and Fieber, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…Animal age in this study was determined by the chronological age as well as the significant decline in performance of reflex behaviors beginning at the age of 12 months ( Figure 2 ). Our laboratory demonstrated that performance in these behaviors declines in a predictable manner with age ( Kempsell and Fieber, 2014 ) and that declining performance is accompanied by a decline in excitability of PVC sensory neurons that control tail withdrawal, decreased short-term facilitation (STF) between tail sensory and motor neurons ( Kempsell and Fieber, 2015 ), decreased expression of ionotropic glutamate receptor subunits ( Greer et al, 2019 ), and other changes in gene expression that alter proteostasis and increase neuro-inflammation ( Kron et al, 2020 ; Kron and Fieber, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, the dearth of functional annotation and lack of even a putative immune gene set makes future inference into the immune response to this novel virus difficult. While some putative immune associated genes have been identified in Aplysia previously in the context of the neuronal transcriptome [14] or aging associated neuro-inflammation [21], these studies did not perform a comprehensive survey of the Aplysia immunome. To address this gap in the Aplysia literature, an in silico survey of Aplysia reference genome was conducted to identify and describe a putative immunome to aid in future immunological studies in this well-established model.…”
Section: Introductionmentioning
confidence: 99%